Enhancing Physics Knowledge for Teaching – Transport properties - Raine, Derek (The University of Hull)
In this session we’ll look at transport properties in fluids. By transport properties we mean the flows that restore a system to equilibrium, so for example, the flow of heat to eliminate a temperature gradient.